2022
DOI: 10.3390/nu14102166
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Characteristics and Influencing Factors on Chinese Immigrants in Canada and the United States: A Scoping Review

Abstract: Background: Chinese immigrants are an integral part of Canadian and American society. Chinese immigrants believe diet to be an important aspect of health, and dietary behaviours in this population have been associated with changes in disease risk factors and disease incidence. This review aims to summarize the characteristics of the dietary behaviours of Chinese immigrants and the associated influencing factors to better inform individual, clinical, and policy decisions. Methods: This scoping review was writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…There were 9 females and 4 males. Professions included physician (12) and dietitian (1). All were practicing in the Metro Vancouver area with 10 in Vancouver and 3 in Burnaby.…”
Section: Participant Demographics: Health Care Providersunclassified
See 2 more Smart Citations
“…There were 9 females and 4 males. Professions included physician (12) and dietitian (1). All were practicing in the Metro Vancouver area with 10 in Vancouver and 3 in Burnaby.…”
Section: Participant Demographics: Health Care Providersunclassified
“…Despite this public health priority to promote F&V consumption, the Canadian Community Health Survey reports in 2021, the number of people in BC who consume F&V 5 or more times per day decreased to 21% ( 11 ). Furthermore, a scoping review of 51 papers found that F&V intake, and fiber among Chinese immigrants in Canada and the United States fall below the national guidelines ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, Chinese immigrants are consuming more morning cereals, pasta, dairy goods, almonds, legumes, and fast food (Martin, Lou, & Sanz Rojo, 2021). According to Zou et al (2022), Chinese immigrants boosted their overall food intake across all food categories and adopted Western foods. The consumption of total calories, meat and substitutes, and carbohydrates rose with acculturation.…”
Section: About Krispy Kreme Incmentioning
confidence: 99%
“…Although these studies reveal the impact of socioeconomic status and cultural differences, most of them implicitly assume that immigrants’ dietary acculturation to the host country's dietary practices is inevitable (Sanou et al., 2014). Despite such a small but growing body of literature, recent scoping reviews reveal that there is still an overwhelming emphasis on individual factors (e.g., individual preferences, and nutritional awareness) and there is a lack of consensus in the dietary acculturation literature (Lee et al., 2021; Zou et al., 2022).…”
Section: Introductionmentioning
confidence: 99%